From Semiconductors to Proteins: Beyond the Average Structure - Billinge, S. J. L.; Thorpe, M. F. (Fundamental Materials Research, 2002)
This series of books, which is published at the rate of about one per year, addresses fundamental problems in materials science. The contents cover a broad range of topics from small clusters of atoms to engineering materials and involve chemistry, physics, materials science, and engineering, with length scales ranging from Angstroms up to millimeters. The emphasis is on basic science rather than on applications. Each book focuses on a single area of current interest and brings together leading experts to give an up-to-date discussion of their work and the work of others. Each article contains enough references that the interested reader can access the relevant literature. Thanks are given to the Center for Fundamental Materials Research at Michigan State University for supporting this series. M.F. Thorpe, Series Editor E-mail: thorpe@pa.msu.edu East Lansing, Michigan, November 200 I v PREFACE The study of the atomic structure of crystalline materials began at the beginning of the twentieth century with the discovery by Max von Laue and by W.H. and W.L. Bragg that crystals diffract x-rays. At that time, even the existence of atoms was controversial